Complete Genome Sequence of the Human Herpesvirus 6A Strain AJ from Africa Resembles Strain GS from North America - Tweedy, J. (Genome Announc, 2015)
The genome sequence of human herpesvirus 6A (HHV-6A) strain AJ was determined in a comparison of target enrichment and long-range PCR using next-generation sequencing methodologies. The analyses show 85 predicted open reading frames (ORFs), conservation with sequenced HHV-6A reference strain U1102, and closest identity to the recently determined GS strain, despite different geographic origins (United States and Gambia).